Walking and stair climbing abilities in individuals after chronic stroke with and without mental health problem - Jaruwan Prasomsri (2015)
Objective: To compare muscle strength, balance, walking and stair climbing abilities among individuals after chronic stroke with or without mental health problems; to describe their physiological response after stress stimulation. Material and Method: Subjects who had their first stroke more than one year ago were classified for mental health problems according to the Depression Anxiety Stress Scale-21. Lower extremity muscle strength of the quadriceps and plantar flexors, was measured by dynamometer. Balance and walking performance was measured by the Berg Balance Scale (BBS), 10-m walk test and timing of stair climbing. Community participation and spiritual well-being were measured. The physiological response of stress stimulation was assessed by the long stress test protocol of the biofeedback device. Results: Forty-five subjects with chronic stroke aged 40-80 years were grouped by with (n = 25) and without mental health problems (n = 20). Significant differences were found in quadriceps muscle strength, BBS, walking and stair climbing speed, community participation and spiritual well-being between two groups. In the stress stimulus phase, the electromyography and heart rate variability demonstrated significant difference between those with and without stress. Conclusion: Individuals with chronic stroke with mental health problems demonstrated decreased quadriceps muscle strength, balance and locomotor performances.